2019
DOI: 10.5194/acp-19-3245-2019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of urban amine-containing particles in southwestern China: seasonal variation, source, and processing

Abstract: Abstract. Amine-containing particles were characterized in an urban area of Chongqing during both summer and winter using a single-particle aerosol mass spectrometer (SPAMS). Among the collected particles, 12.7 % were amine-containing in winter and 8.3 % in summer. Amines were internally mixed with elemental carbon (EC), organic carbon (OC), sulfate, and nitrate. Diethylamine (DEA) was the most abundant among amine-containing particles. Wintertime amine-containing particles were mainly from the northwest direc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…Please refer to Part 1 for details (Chen et al, 2020). Briefly, the field studies were performed simultaneously at Peking University (116.32 • E, 39.99 • N) and Pinggu (117.05 • E, 40.17 • N) from 1 to 29 November 2016 (Fig.…”
Section: Sampling Sites Instrumentation and Data Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Please refer to Part 1 for details (Chen et al, 2020). Briefly, the field studies were performed simultaneously at Peking University (116.32 • E, 39.99 • N) and Pinggu (117.05 • E, 40.17 • N) from 1 to 29 November 2016 (Fig.…”
Section: Sampling Sites Instrumentation and Data Analysismentioning
confidence: 99%
“…1). The detailed description of these two sites is available from Chen et al (2020). The two sites represent both typical urban and rural areas respectively.…”
Section: Sampling Sites Instrumentation and Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…As found previously (Wang et al, 2014), Amine-rich particles are generally very hydrophilic with the highest detection probability occurred within GF >1.5 range. Short alkyl chain aliphatic amines are basic and have relatively high vapor pressures, therefore their presence in particles most likely occur in the form of aminium salts, whose formation is greatly favored in the presence of particulate water (Angelino et al, 2001;Chen et al, 2019). It is found that 77% Amine-rich particles were internally mixed with sulfate or nitrate.…”
Section: Particle Types and Gf Distributionsmentioning
confidence: 99%